Understanding negotiation in airtime sharing in low-income microenterprises - Sambasivan, Nithya; Cutrell, Edward; Cutrell, Ed (CHI 2012: Proceedings of the Conference on Human Factors in Computing Systems, 2012)
Shared access to airtime is a prominent mode of connectivity access in the developing world. We seek to understand airtime sharing among low-income microenterprises in India (small, low-capital businesses, such as flower sellers and milkmen), that constitute 90% of the total enterprises in India. We introduce social negotiation as the foundation of airtime sharing. We highlight negotiation mechanisms in the microenterprise, showing how shared resources are used towards personal interests amidst tensions and value conflicts, by adapting, modifying, subverting, and repurposing airtime. We then explore the design space of airtime and bandwidth sharing in low-income communities, including designing for negotiation and improving readability of airtime.
Best of CHI honorable mention